Novel Neurocognitive Profile in a Minority of Boys with 47, XXY (Klinefelter Syndrome). Issue 9 (15th December 2022) - Samango-Sprouse, Carole A.; Hamzik, Mary P.; Khaksari, Kosar; Brooks, Michaela R.; Sadeghin, Teresa; Gropman, Andrea L.
ABSTRACT: Introduction: 47, XXY, also known as Klinefelter syndrome, is the most commonly occurring sex chromosomal variation (1:660). The neurocognitive profile of boys with 47, XXY, in addition to verbal abilities, language skills, and general intelligence, has been explored in this study. Methods: Fifty-five participants with 47, XXY were segregated into groups according to their performance on the Wechsler Intelligence Scale for Children (WISC): (1) those with a higher performance intelligence quotient (PIQ) in comparison with their verbal IQ (VIQ) and (2) those with a higher VIQ compared with their PIQ. Two-tailed independent t tests were completed to analyze group differences. Results: Our study results demonstrate novel findings that one-third of subjects have higher verbal capabilities than perceptual skills. Those participants who showed the typical presentation of 47, XXY with increased PIQ in comparison with their VIQ excelled on perceptual and visual spatial subtests on the WISC and on nonverbal IQ on the Leiter International Performance Scale-III. In addition, it was found that expressive and receptive vocabulary skills were commensurate in both groups, which has not been reported previously. Discussion: To the best of our knowledge, this is the first study to identify an alternative profile of 47, XXY with increased verbal capabilities in comparison with perceptual skills. In addition, previous research has found that boys with 47, XXY often show increased receptive vocabulary skills in comparison with their expressive vocabulary skills early in life. Therefore, our findings of commensurate expressive and receptive vocabulary skills suggest that age may be an impactful factor in vocabulary development. Further research is necessary to determine individualized treatment options for these patients, focusing on the specific cognitive profile they present.